Aplicación La Travelería: Diseño y Planificación de Viajes con Expertos (2023)
The tourism industry sector has several technological applications for specific purposes, from purchasing tickets, reservations, or package purchases; however, trip design and planning largely depend on the user's knowledge and time, so the final experience at the destination may be unfavorable in some cases. La Travelería works to ensure that in all cases, the user has the best experience with a trip designed and planned by experts, hand in hand with the client.